Levitation of posteriorly dislocated intraocular lens: I.V. catheter connected to the vitreotome aspiration - Gu, Ruiping; Guo, Yue; Zong, Yuan; Jiang, Rui; Sun, Zhongcui (Frontiers in Ophthalmology, 2025)
BackgroundTo introduce a new, simple, and affordable technique that uses a 22G intravenous (I.V.) catheter connected to the vitreotome aspiration to lift the intraocular lens (IOLs) off the retina.MethodsThis retrospective, non-comparative, single surgeon, interventional, consecutive case series examined 4 patients (4 eyes) who underwent the surgical procedure from March 12 and October 22, 2023. Reliability, reproducibility, and intraoperative and postoperative complications of the technique were analyzed.ResultsFour patients presenting with posteriorly dislocated IOLs were included. After a complete 23G vitrectomy under wide-angle viewing system or high magnification contact lens, the 22G I.V. catheter was connected to the vitreotome aspiration and active aspiration was applied. When the IOLs were lifted towards the posterior chamber by continuous vacuum aspiration, they were be safely grasped using intraocular forceps and reposited with scleral fixation suturing or removed through a limbal incision. None of the IOLs fell during active aspiration.ConclusionConnection of I.V. catheter with vitreotome aspiration to lift the IOLs off the retina was a new, simple, safe, and affordable technique.